Noise and military service : implications for hearing loss and tinnitus - Humes, Larry; Joellenbeck, Lois M. (Lois Mary), 1963-; Durch, Jane (National Academies Press, 2006)
People serving in the military will, at some point, be exposed to high-intensity noise of various types. Some may develop hearing loss, especially for high-frequency sounds, or tinnitus ("ringing in the ears"), or both, as a result of their noise exposure. Hearing loss or tinnitus incurred or aggravated during military service may qualify verterans for services and financial compensation from the Department of Veterans Affairs (VA). Since World War II, the human and financial cost associated with hearing loss among military veterans have repeatedly drawn attention to noise, hearing loss, and the need for hearing conservation in military settings